Identification of Ripe Levels in Plantain Fruits Using Hue Saturation Intensity (HSI) Color Space Transformation Method - Ade Sidratul Hayat; Muhammad Syukri; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
The study aimed to determine the maturity level of plantain fruit using the Hue Saturation Intensity (HSI) color space transformation method. This study uses the Hue Saturation Intensity (HSI) color space transformation method to classify the level of ripeness of plantain fruit. The results showed that the Hue Saturation Intensity (HSI) color space transformation method was quite good at identifying the ripeness level of bananas based on the high accuracy of the test. Of the 20 fruit samples where ten unripe and ten ripe plantains were calculated, the maximum and minimum average values of H and S obtained conformity accuracy of 85%.